Piotr Skarga jako wydawca i interpretator Bogurodzicy - Wichowa, Maria (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2013)
Piotr Skarga has played an important role in the history of the reception of Bogurodzica editing three times and interpreting this song. He reprinted this poem in Żywoty Świętych (1579), in Kazania o siedmiu sakramentach (1600) and Kazania przygodnych (1610). Besides these editorial actions he has developed a separate sermon about Bogurodzica. As a publisher he tried to reprint the lyrics faithfully but he was not a passive editor, who dispassionately, with a distance stalks to the form of the text. He was an active didactic, who aimed this old artwork written in medieval Polish to make fully understandable to the modern reader. Therefore, he added the informative and instructive comments on the Bogurodzica. Skarga wanted to inform the reader about life, work, and the way to holiness of Bishop Wojciech, the alleged author of the Bogurodzica, and give the editorial explanation to the poem; to popularize and extend its vitality. Skarga’s comment has also Counter-Reformative overtone. Jesuit preacher by spreading the cult of Mary emphasized the ideological Polish religiosity after Trident, unchanged from the baptism of Poland. Bogurodzica was to provide the fact that from the beginning of Christianity, there was half an ancient hymn that proclaims devotions to Maria, a tradition which continued uninterrupted despite the spread of different faith doctrines. Skarga as an interpreter of the Bogurodzica explains this poem in a simple way, fully comprehensible to his contemporary readers, however, do not trivialize the depth of theological interpretation of this monumental poem. He used a simple style, avoiding ornamentation and stylistic tropes. He turned out to be a discerning commentator of this venerable monument of our poetry, excellent didactics who proclaim in a clear and accessible way The Word of God, closed in a difficult to understand medieval text.